NEW FREEZE DRIED RASPBERRY PRODUCTS - Janković, Miodrag; Bukvić, Branka; Zlatković, Branislav; Stevanović, Snežana; Vukosavljević, Predrag (Economics of Agriculture, 2006)
Freeze drying is relatively new process for drying fruit from frozen state. In distinction from classical drying, freeze drying make product with very little content of water, against maximal preservation of all nutritive matter in the product. These process is especially good for sensitive fruits at whom shall almost save typical flavor, color and vitamins. In this paper oversight of new raspberry products that can bee obtained by freeze drying process is given. Analysis of technological procedures for obtaining of whole freeze dried raspberry and freeze dried raspberry juice in powdered form is given. These technologies are relatively new in the world and with us still are not apply in industrial dimensions.